The key to extraordinary - Lloyd, Natalie (New York, NY : Scholastic Press, 2016)
Twelve-year old orphan Emma Casey lives by a haunted graveyard in her Tennessee town, giving tours, and helping her brother and Granny Blue with the family bakery, and waiting for the destiny dream of her ancestors--but when it comes it shows her only a key, and she finds that she must solve a ghostly mystery that has haunted her town for generations.
Keywords: Haunted cemeteries -- Juvenile fiction; Dreams -- Juvenile fiction; Treasure troves -- Juvenile fiction; Orphans -- Juvenile fiction; Families -- Tennessee -- Juvenile fiction; Tennessee -- Fiction; Haunted places -- Fiction; Ghosts -- Fiction; Dreams -- Fiction; Buried treasure -- Fiction; Orphans -- Fiction; Family life -- Tennessee -- Fiction; Tennessee -- Fiction